Characterization of selenium‐containing glutathione transferase zeta1–1 with high GPX activity prepared in eukaryotic cells. Issue 1 (11th December 2012) - Yin, Li; Song, Jian; Board, Philip G.; Yu, Yang; Han, Xiao; Wei, Jingyan
<x xml:space="preserve">Abstract</x> Accumulating evidence shows that glutathione peroxidase (GPX, EC.1.11.1.9), one of the most important antioxidant selenoenzymes, plays an essential role in protecting cells and tissues against oxidative damage by catalyzing the reduction of hydrogen peroxide by glutathione. Unfortunately, because of the limited availability and poor stability of GPX, it has not been used clinically to protect against oxidative stress. To overcome these problems, it is necessary to generate mimics of GPX. In this study, we have used directed mutagenesis and the inclusion of a selenocysteine (Sec) insertion sequence to engineer the expression in eukaryotic cells of human glutathione transferase zeta1–1 (hGSTZ1–1) with Sec in the active site (seleno‐hGSTZ1–1). This modification converted hGSTZ1–1 into an active GPX and is the first time this has been achieved in eukaryotic cells. The GPX activity of seleno‐hGSTZ1–1 is higher than that of GPX from bovine liver, indicating Sec at the active site plays an important role in the determination of catalytic specificity and performance. Kinetic studies revealed that the ping–pong catalytic mechanism of Se‐hGSTZ1–1 is similar to that of the natural GPX. Copyright © 2012 John Wiley & Sons, Ltd.